Laying the Groundwork for a Fatwa on Autism and Marriage: A Conceptual and Legal Exploration in the Malaysian Context - Dahaman, Mohd Akram; Ibrahim, Basri; Cusairi, Rafidah Mohamad (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
As individuals with autism mature, they eventually reach the age for marriage, influenced by biological desires or cultural practices. In Islamic jurisprudence, autism is linked to the concept of `awarid ahliyyah (legal capacity impediments), which refers to obstacles to legal capacity, whether due to natural conditions such as insanity, idiocy, or forgetfulness, or from human factors like ignorance.